Impact of Oxidative Stress on Hemorheological Parameters in Patients with Acute Poisonings by Psychopharmacological Agents - M. V. Belova; K. K Ilyashenko; I. A. Burykina; Ye. Ye. Bitkova; Ye. A. Luzhnikov; V. B. Khvatov (Общая реаниматология)
Objective: to evaluate the impact of oxidative stress intensity on hemorheological parameters in acute poisonings by psychopharmacological agents. Subjects and methods. The blood values of lipid peroxidation (LPO) and the antioxidant system (AOS), and hemorheological parameters were determined in 196 patients with acute poisoning by psychopharmacological agents. Results. Mild poisoning was accompanied by a moderate rise in peroxidation processes, by compensated antioxidant activity, and by a decrease in hemorheological parameters. In moderate poisoning, and severe one in particular, there was an increase in the LPO/AOS imbalance attended by increases in the viscosity characteristics of blood and plasma and in the aggregation activity of platelets and red blood cells. Conclusion. As the intensity of oxidative stress increases, there are more severe impairments in blood viscosity and aggregation properties, the leading mechanism of which is damage to blood cells due to higher stiffness of their membranes and to plasma release of large-disperse molecules under the action of an excess of LPO products. Key words: oxidative stress, acute poisonings, hemorheology.